Theoretical Study of Terminal Vanadium(V) Chalcogenido Complexes Bearing Chlorido and Methoxido Ligands - Samuel Tetteh; Ruphino Zugle (Journal of Chemistry)
Solvent (methanol) coordinated vanadium(V) chalcogenido complexes bearing chlorido and methoxido ligands have been studied computationally by means of density functional (DFT) methods. The gas phase complexes were fully optimized using B3LYP/GEN functionals with 6-31+G⁎⁎ and LANL2DZ basis sets. The optimized complexes show distorted octahedral geometries around the central vanadium atom. The ligand pπ-vanadium dπ interactions were analyzed by natural bond order (NBO) and natural population analyses (NPA). These results show strong stabilization of the V=O bond as was further confirmed by the analyses of the frontier molecular orbitals (FMOs). Second-order perturbation analyses also revealed substantial delocalization of lone pair electrons from the oxido ligand into vacant non-Lewis (Rydberg) orbitals as compared to the sulfido and seleno analogues. These results show significant ligand-to-metal charge transfer (LMCT) interactions. Full interaction map (FIM) of the reference complex confirms hydrogen bond interactions involving the methanol (O-H) and the chlorido ligand.